The Swahili : Reconstructing the History and Language of an African Society, 8-15 - Nurse, Derek (Book collections on Project MUSE., 1985)
"As an introduction to how the history of an African society can be reconstructed from largely nonliterate sources, and to the Swahili in particular, . . . a model work."-International Journal of African Historical Studies.